Turkish and eu security cultures in perspective: Why do we need a holistic approach to european security? - CEBECİ, Münevver (My University, 2014)
This article argues that Turkey and the EU do not have homogenous security cultures; however, their divergences are not greater than those among EU Member States as well as those between the EU and its members. The article pursues this argument by comparing and contrasting Turkey’s and the EU’s security cultures through the employment of a constructivist ontology and the conceptual frameworks of securitization and desecuritization. It first gives a conceptual overview, defining the terms “security culture”, “holistic approach to security” and “European security”. Then, it analyses Turkey’s and the EU’s security cultures separately, looking into their processes of securitization and desecuritization. Finally, it compares these two distinct security cultures with a view to showing that their differences are not that grave to impede the creation of a common European security culture with the involvement of Turkey. This article concludes that there is need for a holistic approach to European security in order to deal with today’s multi-layered, cross-border, and complex challenges, and, any arrangement which excludes Turkey in this regard, would render European security incomplete.
Keywords: Turkey, European Union, Security Cultures, Holistic Approach to Security, European Security, Securitization, Desecuritization